Perspectives on Pornography - Bloom, Clive. author. aut Link
IX, 178 p.
Keywords: Dealing with moral, political and sexual tensions, this volume provides a forum for male/female dialogue concerning the history, dissemination and consequences of pornographic representaion in film and literature, aiming to challenge established views and inspire further exploration and debate.